Effect of spiritual care education on the spiritual health of preeclamptic women with postpartum stress disorder - Mahboobe Gholami; Mahin Tafazoli; Zahra Mohebbi-Dehnavi; Zahra Kamali (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Spiritual health in the field of health has a great importance in mental disorders and posttraumatic stress disorders, in treatment process. The present study was done aiming "determine the effect of spiritual care education on the spiritual health of preeclamptic women with postpartum stress disorder." MATERIALS AND METHODS: This randomized clinical trial was done in 2017 on 260 women with preeclampsia in Mashhad. Data collection was done with questionnaires Perinatal Posttraumatic Stress Questionnaire (PPQ), the posttraumatic disorder checklist, Duke University Religion Index, and the Spiritual Well-Being Scale (SWBS). In the intervention group, first, women were educated on spiritual care each day based on Richards and Bergin's pattern, in three sessions, which lasted 45-60 min. The control group also received routine cares. All units completed the questionnaire SWBS at the 8th postpartum period. P < 0.05 was meaningful. RESULTS: After the intervention, this score of spiritual health in the intervention and control groups had a significant difference with independent test (P = 0.004). Spiritual health significantly increased in the interventional group. CONCLUSIONS: Providing spiritual care to pregnant mothers with preeclampsia, increase their spiritual health.